Socio-demographic determinants of obesity indexes in Iran:findings from a nationwide STEPS survey - Ali-Asghar Kolahi; Alireza Moghisi; Yalda Soleiman Ekhtiari (Tabriz University of Medical Sciences, 2018)
Background: Overweight and obesity are considered as non-communicable diseases (NCDs)risk factors with increasing prevalence worldwide. This nationwide study aimed to determine the socio-demographic determinants of obesity indexes in Iran. Methods: This cross-sectional study was conducted based on data from the sixth round of nationwide Stepwise approach to surveillance (STEPS) survey in the 31 provinces of Iran in 2011. A total of 9878 people aged ≥20 years were selected using a multi-stage cluster sampling method. Data were collected through three steps questionnaire including ecological, physical and biochemical measurements. We assessed body mass index (BMI), waist circumference(WC) and waist-hip ratio (WHR) as the main indicators of obesity. Results: In this study, the weighted prevalence of overweight and obesity were 34.5% (95% CI:33.6, 35.5) and 21.5% (95% CI: 20.7, 22.3), respectively. The mean ± standard deviation (SD)of BMI among men and women were 25.4±4.4 and 26.9±5.2 kg/m2 respectively. Older age,living alone, having lower education level, being housewife or retired were associated with overweight and obesity (P<0.05). Urbanization was positively associated with BMI and WC.Being obese or overweight was associated with having a history of type 2 diabetes mellitus (T2DM), hypertension (HTN) and cardiovascular diseases (CVDs). Conclusion: The prevalence of overweight in this study was less than global rate while it was vice versa for obesity prevalence. Some socio-demographic characteristics were identified as determinants of obesity which should be considered for planning preventive and control action plans.